IDENTIFICATION AND INITIAL CARE PROCESS OF CHILD VICTIMS OF TRANSNATIONAL TRAFFICKING: A SOCIAL WORK PERSPECTIVE - Warria, Ajwang’; Nel, Hanna; Triegaardt, Jean (Social Work/Maatskaplike Werk, 2014)
Child trafficking violates children’s rights and undermines their protection. Under-identification of child victims of trafficking has been reported to be a challenge globally and in South Africa. This article illustrates the process a social worker could apply when identifying child victims of transnational trafficking. Findings of the qualitative research reveal that there is no single point of entry for a trafficked child and thus there can be several actors in the identification process; it was also found that initial care and protection are also essential. The role of social workers in the identification-assessment-care process is highlighted.